2018
DOI: 10.1038/s41419-018-0526-9
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 but not monomeric IgE regulates FcεRI levels and cell survival in primary human basophils

Abstract: Binding of allergen-specific IgE to its primary receptor FcεRI on basophils and mast cells represents a central event in the development of allergic diseases. The high-affinity interaction between IgE and FcεRI results in permanent sensitization of these allergic effector cells and critically regulates their release of pro-inflammatory mediators upon IgE cross-linking by allergens. In addition, binding of monomeric IgE has been reported to actively regulate FcεRI surface levels and promote survival of mast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Confirming Western blot results by flow cytometry analysis, we showed that low concentrations of IL‐3 significantly and dose‐dependently upregulated MRGPRX2 surface expression after 30 minutes in both granulocyte types. Our data pointing to a pivotal role of IL‐3 in enhancing MRGPRX2 expression are in line with recent observations that IL‐3 transcriptionally regulates surface levels of FcεRI in human primary basophils . Moreover, in most assays measuring basophil functions, IL‐3 appears to be among the most potent (complete or incomplete) agonists and is also a well‐known agonist for eosinophils .…”
Section: Discussionsupporting
confidence: 89%
“…Confirming Western blot results by flow cytometry analysis, we showed that low concentrations of IL‐3 significantly and dose‐dependently upregulated MRGPRX2 surface expression after 30 minutes in both granulocyte types. Our data pointing to a pivotal role of IL‐3 in enhancing MRGPRX2 expression are in line with recent observations that IL‐3 transcriptionally regulates surface levels of FcεRI in human primary basophils . Moreover, in most assays measuring basophil functions, IL‐3 appears to be among the most potent (complete or incomplete) agonists and is also a well‐known agonist for eosinophils .…”
Section: Discussionsupporting
confidence: 89%
“…Here, we identified a discrete population of CCR3 high SSC low basophils in the blood of patients with ovarian cancer of diverse histologies and treatment histories ( Table S3 ). Like basophils from healthy and atopic individuals [ 60 , 61 , 62 , 63 , 64 ], the basophils from ovarian cancer patients also expressed cell-surface FcεRI, which were partly occupied by endogenous IgE. Having confirmed this basophil phenotype, we showed that patient-derived basophils were susceptible to activation by IgE- and non-IgE-mediated stimuli irrespective of prior anti-cancer therapy.…”
Section: Discussionmentioning
confidence: 53%
“…The gamma and beta chains are for maturation and transport of the receptor, whereas the alpha chain contains two extracellular asymmetric binding sites and binds the fragment crystallizable (Fc) region of the IgE-ab. The beta and gamma regions are phosphorylated upon crosslinking of IgE and signals for activation and degranulation of the cell [21]. There is an equilibrium between free IgE-abs and FceRI expression on mast cells and basophils since IgE stabilizes FceRI, which means that a reduction in free IgE leads to a reduction in FceRI expression [21].…”
Section: The High Affinity Ige-receptor Fcerimentioning
confidence: 99%
“…The beta and gamma regions are phosphorylated upon crosslinking of IgE and signals for activation and degranulation of the cell [21]. There is an equilibrium between free IgE-abs and FceRI expression on mast cells and basophils since IgE stabilizes FceRI, which means that a reduction in free IgE leads to a reduction in FceRI expression [21].…”
Section: The High Affinity Ige-receptor Fcerimentioning
confidence: 99%
See 1 more Smart Citation